Cloacal Malformations: Technical Aspects of the Reconstruction and Factors Which Predict Surgical Complexity - Wood, Richard J.; Reck-Burneo, Carlos A.; Levitt, Marc A. (Frontiers in Pediatrics, 2019)
Cloacal malformations are rare anomalies which occur in 1 in 50 000 live births. Anatomically these anomalies are defined by the presence of a single perineal orifice. There is however a substantial range in their complexity. Defining these differences is key to surgical planning and timely referral of selected cases to centers with the capabilities to manage the most challenging cases. Traditionally the common channel length as measured during cysto-vaginoscopy has been used to differentiate between patients that can be repaired with a reproducible operation and those requiring a more complex repair. The quality and range of imaging available has advanced and thus a more detailed anatomic picture is now possible to help with pre-operative planning. Cross sectional imaging with 3D reconstruction has enhanced the understanding of the anatomic variations in these patients. In addition, the sacral ratio, previously thought to only have an influence on long term continence predictions, has been shown to not only forcast the presence of urological anomalies, but also the complexity of the malformation. In principle, cloacal malformations have two major components to the reconstruction. First, the rectum needs to be separated from the urogenital tract and second, the urogenital sinus needs to be managed to create a urethral orifice and vaginal introitus. The length of the urethra has been shown to be vital in deciding between the two main surgical maneuvers; a total urogenital mobilization (TUM) and a urogenital separation. The technical demands of a urogenital separation are significant and discussed here in detail. The need for vaginal replacement adds further complexity to the care of these patients and has also been shown to be related to the length of the urethra. Predicting complexity in an accurate and non-invasive way will facilitate the care of the most complex cloacal malformations and improve outcomes.